IDENTIFIKASI BAKAT USIA DINI SISWA SD – SMP SURAKARTA - Islahuzzaman Nuryadin (PAEDAGOGIA, 2010)
The purpose of execution activity seed to identify athletic talent of candidatesatlet potential to be constructed with erudite approach and watched by growth accuratelyand also kontinue. This research use descriptive method. Seed object is students whichhave achievement school is each goodness mounted by elementary school (SD) and alsojunior high school (SMP) which have age to among/ between 11 year up to 15 year in townof Surakarta. As for to the number of student is 400 student. Technique the usedmeasurement and tes with tes pilotage of talent model Sport Search. Data of measurementadapted for by set of existing size measure in computer later then analysed with techniqueanalyse pilotage of talent model Sport Search (computer software). Result of fromcomputer analysis continued tabulationly with statistical technique diskriptif. Result ofathletic talent potency analysis student shall be as follows: Talent student potency SD andSMP in Surakarta there is 8 good category student, 71 student enough, 171 student less,159 student less once, its meaning there is 8 student which have potency to be constructedas candidate of atlet.